PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF SCREENCAST O-MATIC BAGI SISWA SMP (JURNAL LEMMA, 2021)
Â The pandemic has brought about many educational changes. Distance learning has demanded teachers be more creative in teaching. This study aims to develop interactive learning media using the Screencast O Matic application on opportunity materials for class VIII students. This research is development research with a 4D development model design. The samples in this development research were mathematics educators and class VIII students. This development research includes learning design experts, learning experts, media experts, practitioner experts, educator users, and student users. The data analysis used in this development research is quantitative and qualitative. Quantitative data were obtained from scores obtained from product validation questionnaires and qualitative data obtained from comments and suggestions on product validation questionnaires. From the study results, in the needs analysis of 2 educators and 68 students, the percentages were 86% and 84%, respectively, with the conclusion that educators and students agree with the development of interactive media. From the assessment results, the experts obtained an average of 4.5. As for the users of mathematics educators and ten students of class VIII MTs. Get an average of 4.7. The average achievement of the overall assessment is 4.6. So from these results, it can be concluded that the learning media product uses the automatic screencast application and is declared valid and feasible.